Dukungan Keluarga terhadap Kepatuhan Mengambil Obat Arv pada Odha di Puskesmas Sukaraja Kota Bandar Lampung - Arizwansyah Arizwansyah; Dessy Hermawan; Lolita Sary (Malahayati Nursing Journal, 2023)
ABSTRACT The number of visits by patients who take ARV drugs at 6 Puskesmas in Bandar Lampung City every month was found. It found that there were 66 people in Kedaton Health Center, 64 people in Sukabumi Health Center, 53 people at Pasar Ambon Health Center, and 148 people at Gedong Air Health Center. Moreover, there were 190 people at Simpur Health Center and 107 people at Sukaraja Health Center. There were eight people (7.5%) at the Sukaraja Health Center who did not comply with taking ARV drugs. This study aimed to determine the relationship between family support and compliance to taking ARV drugs for PLWHA (People Living With HIV/AIDS) at the Sukaraja Health Center Bandar Lampung City in 2022. This type of research is quantitative with a cross-sectional approach. The population in this study were all patients who visited and took ARV drugs at the Sukaraja Health Center every month, totaling 107 people. Sampling in this study uses accidental sampling. The results of the univariate analysis obtained good emotional support (69.2%), good instrumental support (61.7%), good information support (53.3%), good appreciation support (58.9%), and respondents adherent to taking ARV drugs (50.5%). While based on the bivariate analysis, it was known that p-value value (0.05), namely emotional support (0.010), instrumental support (0.000), informational support (0.024), and reward support (0.001 ). The results of the logistic regression test showed that the most dominant effect of award support on adherence to ARV drugs with Exp (B) was 4,397. It is hoped that it can It is hoped that it can increase the provision of award support in the form of praise, enthusiasm and attention to PLWHA for the continuity of ARV treatment. Keywords : Family Support, Adherence, ARV Medicine  ABSTRAK Jumlah kunjungan pasien yang mengambil obat ARV di 6 Puskesmas di Kota Bandar Lampung setiap bulannya didapatkan di Puskesmas Kedaton ada 66 orang, Puskesmas Sukabumi ada 64 orang, Puskesmas Pasar Ambon ada 53 orang, Puskesmas Gedong Air ada 148 orang, Puskesmas Simpur terdapat 190 orang dan Puskesmas Sukaraja ada 107 orang. Puskesmas Sukaraja tercatat sebanyak 8 orang (7,5%) yang tidak patuh mengambil obat ARV. Tujuan dari penelitian ini untuk mengetahui hubungan dukungan keluarga terhadap kepatuhan mengambil obat ARV pada ODHA di Puskesmas Sukaraja Kota Bandar Lampung tahun 2022.Penelitian kuantitatif dengan pendekatan cross sectional. Populasi dalam penelitian ini adalah seluruh pasien yang berkunjung dan mengambil obat ARV di Puskesmas Sukaraja setiap bulan dengan jumlah 107 orang. Pengambilan sampel menggunakan accidental sampling. Hasil analisis univariat, didapatkan dukungan emosional yang baik (69,2%), dukungan instrumental yang baik (61,7%), dukungan informasi yang baik (53,3%), dukungan penghargaan yang baik (58,9%) dan responden patuh mengambil obat ARV (50,5%), sedangkan hasil analisis bivariat diketahui ada hubungan dukungan emosional, instrumental, informasi dan penghargaan terhadap kepatuhan mengambil obat ARV dengan p-value nilai α (0,05) yaitu dukungan emosional (0,010), dukungan instrumental (0,000), dukungan informasi (0,024) dan dukungan penghargaan (0,001) dan hasil uji regresi logistic menunjukkan dukungan penghargaan yang paling dominan pengaruhnya terhadap kepatuhan mengambil obat ARV dengan Exp (B) 4,397. Diharapkan dapat meningkatkan pemberian dukungan penghargaan berupa pujian, semangat dan perhatian kepada ODHA guna kesinambungan pengobatan ARV. Kata Kunci: Dukungan Keluarga, Kepatuhan, Obat ARV